Direct medical costs of congenital heart surgery for isolated lesions in Rwanda. - Yayehyirad Ejigu; Vongai C Mlambo; Kara L Neil; Yihan Lin; Augustin Sendegeya; Stella M Umuhoza; Josue Murengezi; Corneille Ntihabose (PLOS Global Public Health, 2025)
Cost transparency is important to facilitate national health infrastructure planning for pediatric cardiac surgery in low-resourced settings. The aim of this paper is to determine direct medical costs of common pediatric congenital heart procedures performed by an in-house cardiac surgery program in Rwanda. Billing information for patients with isolated congenital heart disease who underwent surgery between October 2022 and April 2024 was collected from the hospital management system. Charges were organized into 10 categories, including procedure cost, theater medications and consumables, intensive care unit and ward expenses, anesthesia fees, hospital charges, room charges, testing, and ancillary services. Linear regression was performed to identify perioperative factors associated with increased costs. Costs were converted from Rwandan Francs to US Dollars using the exchange rate 1 USD = 1,262 RWF on 1 January 2024. 117 patients received 8 types of surgeries. Median costs ranged from USD$1,969.04 for patent ductus arteriosus ligation to USD$18,239.00 for arterial switch operation. Excluding the latter, the cost of surgeries was USD$7,662 or less. Theater medications and consumables were the most expensive category accounting for 44.6% (USD$3,071.28) of total costs. This was followed by the cost of cardiothoracic procedure itself which constituted 15.4% (USD$810.90) of total costs. Prolonged hospital stays and operative times increased costs by USD$172.57 and USD$1,015.35 (p < 0.001), respectively. Complications and lesion complexity did not independently predict increased costs (p > 0.05). Direct medical costs of pediatric congenital heart surgeries in Rwanda are generally lower than the mean USD$7,366 plus travel expenses charged abroad. Costs can be lowered by reducing per unit costs of theater consumables and ensuring timely discharge.